Teknik Walking Tandem dan Pengaruhnya terhadap Depresi pada Lansia - Hartati, Hartati; Handoyo, Handoyo; Prasetyo, Herry (Journal of Bionursing, 2024)
ABSTRACT Background: Psychological problems are health issues that cause changes in emotions, thoughts, and behavior in older people. These conditions have a negative impact on the elderly in daily life, especially in their families and social activities. The prevalence of mental disorders in the elderly, especially depression, is increasing along with the increasing number of older people. Some ways to overcome elderly depression are by involving the elderly in new activities that they like, learning to adapt to change, feeling connected to a community of social interaction, and staying physically active. One of the most possible activities is walking with the tandem method. Aim:The aim of this study was to determine the effect of the Walking Tandem technique on depression in the elderly in the Mersi village area of Banyumas regency. Method:The research method is a quasi-experiment with pre and post test design approach. 60 respondents were taken by simple random sampling. Respondents were divided into two groups: treatment and control groups. The treatment group was given treatment with the application of walking tandem for two times a week for two months, while the control group was carried out with regular walking activities. The instrument used to measure the level of elderly depression is the Geriatric Depression Scale (GDS) short form. The data analysis used was an independent t test and Paired t test. Results: The results of this study indicate that there is a significant effect of the walking tandem technique on depression in the elderly, with a p value of 0.00 is < α = 0.05. Conclusions and suggestions:: The application of walking tandem technique can reduce score depression in the elderly people. By continuing treatment in applying walking tandem could prevent the increasing of Geriatric Depression Scale score in the elderly people. Keywords: Elderly people ,Depression, Waling tandem, Geriatric Depression Scale (GDS)